KONTRIBUSI FAMILY FUNCTION DAN ACADEMIC RESILIENCE TERHADAP STUDENT SUBJECTIVE WELL-BEING PADA SISWA SMP - Ika Budi Nurani; Tri Nai’imah; Fatin Rohmah Nur Wahidah; Eka Rizki Meilani (Jurnal Padamu Negeri, 2025)
Adolescence is a crucial period in individual development, during which students begin to face academic pressure and complex family dynamics. Family function plays a significant role in supporting student subjective well-being. however, challenges such as poor communication, lack of emotional support, and interfamily conflicts can hinder a child's development. Simultaneously, students are also confronted with high academic demands, potentially leading to stress and feelings of inadequacy. This study aims to examine the influence of family function and academic resilience on student subjective well-being among students of SMP Muhammadiyah 48 Cikupa, Tangerang Regency. This is a quantitative study involving 169 students selected through simple random sampling. Data were collected using the Student Subjective Well-Being Questionnaire (SSWQ), the Family Functioning Questionnaire (FFQ), and the Academic Resilience Scale (ARS). The analysis revealed a t-value of 11.247 for the effect of family function on student subjective well-being and a t-value of 12.831 for the effect of academic resilience. The F-value of 93.053 indicates a significant joint influence of family function and academic resilience on student subjective well-being. With an R. Square value of 0.529, the findings suggest that family function and academic resilience, contribute effectively to 52.9% of the vanance in student subjective well-being while the remaining 47.1% is influenced by other unexamined factors. These findings highlight the importance of a supportive family environment and the development of academic resilience in helping students navigate academic stress and maintain psychological well-being.